Posterior Cruciate Ligament and Patellar Tendon Can Predict Anterior Cruciate Ligament Size for Planning During ACL Reconstruction in Pediatric Patients - Nicholas A. Strada, M.D; Emil Stefan Vutescu, M.D; Mohammadali Mojarrad, M.D; Ryan Harrington, M.D; Sebastian Orman, M.D; Peter Evangelista, M.D; Aristides I. Cruz, Jr., M.D., M.B.A (Elsevier, 2023)
Purpose: To establish correlations between the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), and patellar tendon in normal pediatric knees to inform surgical planning for ACL reconstruction graft size. Methods: Magnetic resonance imaging scans of patients ages 8 to 18 years were assessed. Measurements included ACL and PCL length, thickness, and width, and ACL footprint thickness and width at the tibial insertion. Interrater reliability was assessed with a random set of 25 patients. Pearson correlation coefficients were used to assess the correlation between ACL, PCL, and patellar tendon measurements. Linear regression models were used to test whether the relationships differed by sex or age. Results: Magnetic resonance imaging scans of 540 patients were assessed. Interrater reliability was high for all measurements except PCL thickness at midsubstance. Sample equations for estimating ACL size are as follows: ACL length = 22.61 + 1.55∗PCL origin width (R2 = 0.46; 8- to 11-year-old male patients), ACL length = 12.37 + 0.58∗PCL length + 2.29∗PCL origin thickness - 0.90∗PCL insertion width (R2 = 0.68; 8- to 11-year-old female patients), ACL midsubstance thickness = 4.95 + 0.25∗PCL midsubstance thickness + 0.04∗PCL insertion thickness - 0.08∗PCL insertion width (R2 = 0.12; 12- to 18-year-old male patients), and ACL midsubstance width = 0.57 + 0.23∗PCL midsubstance thickness + 0.07∗PCL midsubstance width + 0.16∗PCL insertion width (R2 = 0.24; 12- to 18-year-old female patients). Conclusions: We found correlations between ACL, PCL, and patellar tendon measurements that can be used to create equations that predict ACL size in various dimensions based on PCL and patellar tendon measurements. Clinical Relevance: There is a lack of consensus on the ideal ACL graft diameter for pediatric ACL reconstruction. The findings from this study can assist orthopaedic surgeons to individualize ACL graft size for specific patients.